1994
DOI: 10.2527/1994.723709x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recombinant bovine somatotropin and dietary energy intake on growth, secretion of luteinizing hormone, follicular development, and onset of puberty in beef heifers2

Abstract: The effects of dietary energy and recombinant bovine somatotropin (bST) on pattern of LH release, follicular development, and onset of puberty were studied in 40 Angus heifers. At 7 mo of age, heifers were assigned to a 2 x 2 factorial experiment; the main effects were dietary energy (high [HDE]: 14.15 Mcal of ME/d or moderate [MDE]: 10.84 Mcal of ME/d) and somatotropin (bST; 350 mg every 2 wk or vehicle). Beginning at 9 mo of age, heifers were observed twice daily for estrous activity. From 10.5 to 12 mo of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
3
6

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 38 publications
5
25
3
6
Order By: Relevance
“…In addition, the nutritional level after weaning did affect the frame score size in heifers, as previously demonstrated by Yelich et al, (1996). In agreement, Hall et al (1994) found no differences in height of heifers receiving 14 Mcal day -1 or 10 Mcal day -1 of metabolisable energy. Indeed, the chest circumference showed no relationship with nutritional level and %N degree to reach puberty.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, the nutritional level after weaning did affect the frame score size in heifers, as previously demonstrated by Yelich et al, (1996). In agreement, Hall et al (1994) found no differences in height of heifers receiving 14 Mcal day -1 or 10 Mcal day -1 of metabolisable energy. Indeed, the chest circumference showed no relationship with nutritional level and %N degree to reach puberty.…”
Section: Discussionsupporting
confidence: 77%
“…Diets alter body composition in heifers, indicating that increase in nutrient intake would incrase body size and fatness at puberty (Hall et al, 1994;1995). According to Cassady et al (2009), the body weight or body fat plays an important role in the nutritional status appearance with a close relationship to the reproductive axis.…”
Section: Introductionmentioning
confidence: 99%
“…Hall et al (1994) trabalharam com ganhos de 0,770 e 0,510 kg/dia e não observaram diferença no peso à puberdade (336 e 330 kg, respectivamente).…”
Section: Resultsunclassified
“…35 ' 36 Πρόσφατες έρευνες σε κρεατοπαραγωγικές αγελάδες οδήγησαν στο συμπέρασμα, ότι η bST μπορεί να παίζει σημαντικό ρόλο στην επίδραση της θρεπτικής κατάστα σης στην ωοθηκική λειτουργία κατά την περίοδο της λοχείας, πιθανώς μέσω της αλλαγής της συγκέντρωσης του IGF-1 στα ωοθυλάκια. 37 Σχετικά με το ορμονικό πρότυπο, από ορισμένους ερευνητές δε διαπιστώθηκε καμία αλλαγή στην έκκριση της LH, 38 ενώ από άλλους διαπιστώθηκε, ότι κατά τον πρώτο ωοθηκικό κΰκλο που ακολουθεί τη χορήγηση της bST μεταβάλλεται το πρότυπο έκκρισης της LH, χωρίς όμως να επηρεάζεται η συγκέντρωση της οιστραδιόλης στο αίμα, το μέγεθος των ωοθυλακιων ή η διάρκεια της ωοθυλακικής φάσης του ωοθηκικού κύκλου. 39 Επιπλέον, παρατηρήθηκε μείωση της αναπαραγωγικής δραστηριό τητας, κατά την αρχή της γαλακτικής περιόδου, υστέρα από τη χορήγηση σχετικά υψηλών δόσεων (40mg) bST.…”
Section: επιδράσεις στην αναπαραγωγήunclassified